Identifying adult hypophosphatasia in the rheumatology unit - Feurstein, Julia; Behanova, Martina; Haschka, Judith; Roetzer, Katharina; Uyanik, Gökhan; Hadzimuratovic, Benjamin; Witsch-Baumgartner, Martina; Schett, Georg; Zwerina, Jochen; Kocijan, Roland (Orphanet Journal of Rare Diseases, 2022)
Background: The most frequent manifestation in adult hypophosphatasia (HPP) is musculoskeletal pain. The unspecific nature of its clinical presentation may prevent correct diagnosis. The aim of the study was to assess the prevalence of ALPL mutations in adult patients treated in rheumatological outpatient facilities with evident musculoskeletal symptoms typical for HPP. Methods: Over a period of 10 years 9,522 patients were screened in the rheumatology outpatient clinic of the Hanusch hospital Vienna. Serum ALP levels ≤ 40 U/L were found in 524 patients. After screening for secondary causes, 73 patients were invited for clinical evaluation. Genetic testing was performed in 23 patients with suspected HPP. Logistic regression models with Firth penalisation were used to estimate the unadjusted and BMI-adjusted association of each clinical factor with HPP. Results: Mutations in the ALPL gene were observed in 57% of genetically screened patients. Arthralgia, fractures, and pain were the leading symptoms in individuals with ALPL mutation. Chondrocalcinosis (OR 29.12; 95% CI 2.02–1593.52) and dental disease (OR 8.33; 95% CI 0.93–143.40) were associated with ALPL mutation, independent of BMI. Onset of symptoms in patients with ALPL mutation was at 35.1 (14.3) years, with a mean duration from symptoms to diagnosis of 14.4 (8.1) years. Bone mineral density (BMD) and trabecular bone score (TBS) as well as bone turnover markers were not indicative for HPP or ALPL mutation. Conclusion: HPP can mimic rheumatologic diseases. Thus, HPP should be considered as a possible diagnosis in adult patients presenting with musculoskeletal pain of unknown origin in rheumatology outpatient clinics. In patients with persistently low ALP serum levels and unclear musculoskeletal pain, HPP as the underlying cause has to be considered.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Alkaline phosphatase; ALPL gene; Arthralgia; Hypophosphatasia; Musculoskeletal pain